De Verona à Uberabinha: Trajetória e imagens de um fotógrafo - Simão, Pâmela Aparecida Vieira (2022)
This paper aims to reconstruct the trajectory of the Italian photographer Angelo Naguettini (10/21/1889 - 10/03/1983) seeking to understand his imagetic production as an important part of his path in the city of Uberlândia. It urges us to understand the photo as a social practice circumscribed in a given context and constituted by values and meanings. For this reason, we have elected as primordial the investigation of Angelo Naguettini's life trajectory. We believe that the reconstruction of his trajectory, paying attention to his network of relationships, problematizing his choices, refusals and negotiations may signal important elements in the apprehension of his photographic work. This means, in other words, to value his life itinerary as a crucial point in the understanding of his photographic style. The relationships he established throughout his life, not only professional, but also personal, influenced his way of photographing, as well as, influenced the circulation of his material in the past and also in the present of the city of Uberlândia. We will use varied documents and photos of various themes (reproduced in different supports). The guiding thread that will equalize the selection of what will be highlighted, as well as the work methodology, will be our goal of understanding his photographic legacy articulated to his life story. Such objective is based on our assumption that the subject (photographer, businessman, entrepreneur, father, husband, friend, etc.) cannot be separated from his imagetic collection; on the contrary, they are integrated.